Three‐Dimensional Macroporous NiCo2O4 Sheets as a Non‐Noble Catalyst for Efficient Oxygen Reduction Reactions. Issue 42 (5th September 2013) - Xiao, Ying; Hu, Chuangang; Qu, Liangti; Hu, Changwen; Cao, Minhua
Abstract A facile and low‐cost strategy is developed to prepare three‐dimensional (3D) macroporous NiCo2O4 sheets, which can be used as a highly efficient non‐noble metal electrocatalyst for the oxygen reduction reaction (ORR) in alkaline conditions. The as‐obtained sheets have a thickness of about 150 nm and feature a typical 3D macroporous structure with pore volumes of up to 0.23 cm3 g−1, which could decrease the mass transport resistance and allow easier access of the reactants to the active surface sites. The as‐prepared macroporous NiCo2O4 sheets exhibit high electrocatalytic activity for ORR with a four‐electron pathway, good long‐term stability and high tolerance against methanol. The unique 3D macroporous structure and intrinsic properties may be responsible for their high performance.